PERBURUAN DAN PERDAGANGAN BURUNG CENDERAWASIH DI PAPUA - Suroto, Hari (BALAI ARKEOLOGI PAPUA, 2010)
Cenderawasih is a bird which has the most beautiful fur in the world, which makes this bird is called as the bird of paradise. The habitat of this bird is only located in Papua. The beautiful fur attracted hunter and merchant from outside Papua to come into the island. Cenderawasih became a very important export commodity in Papua by the end of 19th century. This was the period when the market demand increased rapidly because of the fashion development that made the price of cenderawasih also increased. The presence of cenderawasih hunter from outside Papua has made many changes for the Papuan. They started to know the utensils from iron, pottery, timor fabric, the used of Malayan term and mixed marriage.